How to slice: snapshots of Argonaute in action. - Parker, J (2010)
Argonaute is the principal protein component of the mechanisms of RNA silencing, providing anchor sites for the small guide RNA strand and the 'slicer' activity for cleavage of target mRNAs or short passenger RNA strands. Argonaute is the core constituent of the silencing effector complexes RISC (RNA-induced silencing complex) and the RITS complex (RNA-induced initiation of transcriptional gene silencing complex), interacting directly or indirectly with Dicer proteins, R2D2/Loquacious/TRBP and GW182 family proteins in the former, and Chp1 and Tas3 in the latter. In a breakthrough series of papers, Patel et al. provide a set of 'molecular snapshots' of the catalytic cycle of Argonaute, exploiting mismatches and mutants to capture and visualize by X-ray crystallography Argonaute from Thermus thermophilus with guide and target strands at various stages of the silencing process. The structural studies, coupled to structure-directed biochemical analysis, together with other thermodynamic and kinetic studies, provide insights into Argonaute with implications for the mechanisms of RNA silencing in eukaryotes.